Assessment of water stress level about global glacier-covered arid areas: A case study in the Shule River Basin, northwestern China - Wang, Shijin; Zhao, Qiudong; Pu, Tao (Journal of hydrology. Regional studies, 2021)
•Glaciers play important role in the sustainable water use in the global arid area.•The average glacier meltwater of the SRB will decrease 15 % by 2030 (RCP 2.6).•The existence of glacial melt water reduced greatly the water stress of the SRB. The Shule River Basin (SRB) in northwestern China is a representative area of global glacier-covered arid areas. Water resources have greatly influenced sustainable development in global arid regions where glacier runoff is an important component of water resource supply. This study focused on the assessment of the water resources–carrying capacity in the SRB based on the United Nations Sustainable Development Goals (SDGs) indicator 6.4.2, level of water stress (LWS). During the period between 2000 and 2030, the runoff of the SRB was predicted to follow an overall increasing trend. From 2000 to 2020, the annual average runoff in the upper reaches of the SRB was 10.9 × 108 m3, and then from 2021 to 2030, it increased by 22.8 %. According this trend, the average contribution of glacier meltwater to the total basin runoff is expected to decrease from the current 23 % to 15 % by 2030 (Representative Concentration Pathway 2.6, RCP 2.6). The supply of fresh-water resources has been close to the level of demand since 2015 and the LWS may increase between 2021 and 2030. The existence of glacial meltwater is expected to result in the continued reduction of basin water stress in the SRB by an average of 0.71 during the period between 2000 and 2030. Therefore, it is necessary to control water consumption of the socioeconomic system and adjust the industrial structure to face or adapt to the crisis of water shortage in global glacier-covered arid areas.